Introducing Bruner : a guide for practitioners and students in early years education - Smidt, Sandra, 1943- (London : Routledge, 2011)
Covers Bruner's key concepts in relation to early learning and teaching.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Bruner, Jerome S; Early childhood education; Electronic books